Scholars in Exile The Ukranian Intellectual World in Interwar Czechoslovakia - Zavorotna, Nadia (University of Toronto Press, 2019)
Throughout the 1920s and 30s Prague was the intellectual center of Ukrainian émigrés in Europe, not least because of significant financial support from the Czechoslovak government and its first president, Tomáš Garrigue Masaryk, for émigré students and intellectuals. On the basis of extensive archival research in Ottawa, Prague, and Kyiv, Zavorotna outlines the continuation of Ukrainian scholarship in history, linguistics, pedagogy, the visual arts, and other disciplines at various institutions in Prague and Poděbrady. These schools constitute the critical link between Ukrainian intellectual life before World War One and postwar émigré communities in Canada and the United States.